COVID-19 Impact on Healthcare and Supportive Services for People Who Use Drugs (PWUDs) in Malaysia - Vicknasingam, Balasingam; Mohd Salleh, Nur Afiqah; Chooi, Weng-Tink; Singh, Darshan; Mohd Zaharim, Norzarina; Kamarulzaman, Adeeba; Chawarski, Marek C. (Frontiers in Psychiatry, 2021)
Background: Restrictive orders and temporary programmatic or ad hoc changes within healthcare and other supportive systems that were implemented in response to the COVID-19 epidemic in Malaysia may have created hindrances to accessing healthcare and/or receiving other supportive services for people who use drugs (PWUDs). Design: A primarily qualitative study has been conducted to evaluate how service providers and recipients were adapting and coping during the initial periods of the COVID-19 response. Settings: The study engaged several healthcare and non-governmental organizations (NGOs) in the peninsular states of Penang, Kelantan, Selangor, and Melaka. Participants: Medical personnel of methadone maintenance treatment (MMT) programs (n = 2) and HIV clinics (n = 3), staff of NGO services (n = 4), and MMT patients (n = 9) were interviewed using a semi-structured format. Results: Interviewed participants reported significant organizational, programmatic, and treatment protocols related changes implemented within the healthcare and support services in addition to nationally imposed Movement Control Orders (MCOs). Changes aimed to reduce patient flow and concentration at the on-site services locations, including less frequent in-person visits, increased use of telemedicine resources, and greater reliance on telecommunication methods to maintain contacts with patients and clients; changes in medication dispensing protocols, including increased take-home doses and relaxed rules for obtaining them, or delivery of medications to patients' homes or locations near their homes were reported by the majority of study participants. No significant rates of COVID-19 infections among PWUDs, including among those with HIV have been reported at the study sites. Conclusions: Although the reported changes presented new challenges for both services providers and recipients and resulted in some degree of initial disruption, generally, all participants reported successful implementation and high levels of compliance with the newly introduced restrictions, regulations, and protocols, resulting in relatively low rates of treatment disruption or discontinuation at the study sites.